Tales of two Londons : stories from a fractured city (OR Books, 2018)
This anthology sets out to mirror Londons diversity by ensuring that more than a third of the voices are of those not born in the UK. It aims to reflect the fact that any city is the sum of its people, and the intelligence they offer is various and sometimes oblique. How do the triumphs of community activism square with the curse of gentrification? What is it like to give birth shortly after arriving in a strange city? How does Londoners love of cats and dogs feel to someone who has lost everything? Memoir, reportage, history and several different genres of poetry keep company in its pages, sparking off each other in challenging, invigorating and inspiring ways --From the Introduction.